First-principles calculations of zone center phonons and related thermal properties of MgSiN2 - Chaiyawat Kaewmeechai (2018)
© Published under licence by IOP Publishing Ltd. MgSiN 2 semiconductor is alternative material beyond the family of III-N, which is used widely in optoelectronic devices. This work presents the calculations of the dielectric tensor, Born effective charge tensor, phonon frequencies at Γ point, phonon dispersion, Helmholtz free energy (ΔF), internal energy (ΔE), entropy (ΔS) and specific heat capacity at constant volume (C v ) of MgSiN 2 by using the density-functional perturbation theory (DFPT) as implemented in ABINIT. We found that the phonons and thermal properties of MgSiN 2 have similar properties to those of ZnSiN 2 and C v of MgSiN 2 are in agreement with the available experimental results.